RECREATIONAL MARKETING AND ITS UNIQUENESS - SUBACHOV, MYKOLA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
When thinking about vacation, everyone imagines it in their own way. Some people consider active recreation the best, while others consider it passive. Fortunately, marketing in the field of recreation is expanding every day due to human imagination and everyone has at least a few options for leisure. It all depends on the desire.To date, there is not much research in this area, so let's focus on the concept of recreational marketing. This leisure industry provides experience, pleasure, relaxation and even better health.The article analyzes the main definition of recreation marketing and its components that make it unique in terms of the modern day. Marketing research in the area of recreation is particularly relevant, and it is based on a number of new services, brands and products aimed at improving the quality of human life.Summarizing the above, leisure marketing is a truly unique industry. Using certain templates, monitoring software is very important for recreational marketers. Finding the best way and place to relax is done through social media. It is there that consumers have more opportunities to choose the right brand, product or service among thousands of recreational brands. They also have greater access to their services and can interact with brands through companies' social media platforms.
Keywords: recreational marketing; leisure; targeting; marketing template; social network; pecialized social media monitoring software